Analisis Faktor-Faktor Yang Mempengaruhi Permintaan Asuransi BPJS Ketenagakerjaan Pada Pekerja Sektor Formal Kota Probolinggo - Hanafi Ya Muslim; Mohammad Faisal Abdullah; Firdha Aksari (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2022)
This study aims to determine the factors that influence the demand for BPJS Employment insurance for formal sector workers in the city of Probolinggo. This study uses quantitative methods with the analytical tool used is multiple linear regression with EViews9 and SPSS25.0 programs. The results obtained indicate that income, education level, and age have a significant positive effect on BPJS Employment insurance demand.